PENGARUH SUSTAINABILITY ACCOUNTING TERHADAP KINERJA PERUSAHAAN (PADA PERUSAHAAN YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Lely Mulyawati; Yvonne Augustine (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2017)
The purpose is to know the influence of sustainability accounting to firm performance in companies which listed in Indonesia Stock Exchange, in 2011-2015. Sustainability accounting use Guidelines Global Reporting Initiative G4. Firm performance use Return on Sales (ROS), and Return on Equity (ROE). This research uses regression method with Program IBM SPSS 23. The finding are sustainability accounting (economic, environment, and social aspects disclosure) didn’t have a significant positive influence to ROS. Economic, and environment aspects disclosure didn’t have a significant positive influence, but social aspects disclosure have a significant positive influence to Return on Equity.